Appliances of Generative AI-Powered Language Tools in Academic Writing: A Scoping Review - Lilia Raitskaya; Елена Тихонова (Journal of Language and Education)
Introduction: Academic writing is getting through a transformative shift with the advent of the generative AI-powered tools in 2022. It spurred research in the emerging field that focus on appliances of AI-powered tools in academic writing. As the AI technologies are changing fast, a regular synthesis of new knowledge needs revisiting. Though there are scoping and systematic reviews of some sub-fields, the present review aims to aims to set the scope of the research field of research on GenAI appliances in academic writing.